Management of the property of women’s religious institutes in Ivory Coast : rigor and transparency in the face of the african mentality - (:unkn) unknown (My University, 2022)
The Catholic Church in Africa is confronted with all kinds of abuses related to the administration of ecclesiastical goods that are essential for the Church's mission. These financial abuses do not only concern dioceses, but also religious institutes whose goods must be managed according to the norms. The present research studies women's institutes in the Ivory Coast to see how they apply appropriate norms to the management and protection of ecclesiastical goods. As certain aspects of the « African mentality » may encourage a lack of rigour and transparency in management, the emphasis has to be on the correct application of universal and proper law, on vigilance at all levels, the need for awareness of the importance of rigorous management, and coherence between personal and community life with the vow of poverty.
Keywords: African Research